Relationship between Erk1/2 signal pathway and nerve cell apoptosis rats with ischemic stroke - Gao, Xiaorong; Li, Haijun; Dong, Zhiyan; Zhang, Pengxuan; Liu, Rui; Xue, Yidong; Shi, Ning (Cellular and Molecular Biology, 2019)
To investigate the relationship between the Erk1/2 signal pathway and neuronal apoptosis in ischemic stroke rats. Male SD(Sprague Dawley) rats (n = 24) were randomly divided into three groups, each containing 8 rats: sham-operated group, MCAO(Midle cerebral artery oclusion) group, and MCAO + U0126 intervention group (U0126 group). In in vitro trial, primary cortical nerve cells were divided into three groups: control group, OGD(Oxygen and glucose deprivation) group, and U0126 intervention group (U0126 group). In vivo protein expression levels of Erk1/2, p-Erk1/2 and Bcl-2 were determined using western blot. The expressions of Bcl-2, Bcl-xl and Bax were assayed using immunohistochemical staining. Nerve cell mortality in cerebral tissue was detected using TUNEL staining. In in vitro trials, cell apoptosis was assayed with flow cytometry and LDH release. The activity of caspase-3 was determined. Nerve cell apoptosis was determined using Hoechst33258 staining method. In in vivo trial, it was found that the protein expression level of p-ERK1/2 in cerebral tissue in the MCAO group was significantly increased, when compared with that of the sham-operated group, while the protein expression level of p-Erk1/2 in the U0126 group was significantly lower than that in the MCAO group. The expression levels of Bcl-2 and Bcl-xl in the MCAO group were significantly lower than the corresponding expression levels in the sham-operated group, while the expressions of Bcl-2 and Bcl-xl in the U0126 group were significantly lower than those in MCAO group. In MCAO group, the expression of Bax was significantly higher than that in the sham-operated group, while Bax expression was higher in U0126 than in MCAO group. There were significantly higher number of dead nerve cells in MCAO group than in the sham-operated group, while nerve cell mortality in U0126 group was significantly lower than in MCAO group. In in vitro trials, flow cytometry revealed significantly higher apoptosis of OGD-treated nerve cells, relative to the control group. Nerve cells exposed to U0126 and treated with ODR (Oxygen-dependent repressor) were significantly decreased in population, when compared with single OGD treatment group. The LDH release level of nerve cells treated OGD was significantly increased, when compared with that of the control group. However, LDH release level of nerve cells treated with OGD after U0126 intervention was significantly decreased, relative to the single OGD treatment group. The dilution of nerve cell nucleus after OGD treatment was significantly increased, when compared with that of the control group. For nerve cells treated with ODR after U0126 intervention, the nuclear dilution was significantly decreased, relative to that of nerve cell nucleus in the single OGD treatment group. The OGD treatment led to significant increase in nerve cell caspase-3 activity, relative the control group. However, the caspase-3 activity of nerve cells treated with ODR after U0126 intervention was significantly decreased, when compared with single OGD treatment group. The activation of Erk1/2 signal pathway during ischemic stroke promotes apoptosis of nerve cells. Based on these findings, it can be reasonably inferred that the ERK1/2 signal pathway may be an important target for treating ischemic stroke.